Race reporting and disparities in clinical trials on Alzheimer's disease: A systematic review. (June 2019) - Canevelli, Marco; Bruno, Giuseppe; Grande, Giulia; Quarata, Federica; Raganato, Riccardo; Remiddi, Francesca; Valletta, Martina; Zaccaria, Valerio; Vanacore, Nicola; Cesari, Matteo
Highlights: Race is an important health determinant. Race is insufficiently considered in research protocols targeting AD. Race may influence the efficacy and safety profiles of anti-dementia medications. Blacks and Hispanics are underrepresented in clinical trials on AD. The collecting and reporting of data on race should be improved. Abstract: Introduction: Race is an important health determinant and should adequately be considered in research and drug development protocols targeting Alzheimer's disease (AD). Methods: A systematic review of available randomized controlled trials (RCTs) on the currently marketed treatments for AD was conducted with the aim of 1) documenting the reporting of race, and 2) exploring the impact of race on the efficacy and safety/tolerability of the considered medications. Results: Overall, 59.2% of the 49 retained RCTs reported information concerning the race of participants. Only a striking minority of enrolled patients was constituted of blacks and Hispanics. None on the retained studies reported results on the efficacy and safety/tolerability of the tested treatment separately for racial groups nor performed sensitivity analyses accounting for the race of participants. Discussion: Race has insufficiently been reported in previous interventional studies on AD. Its potential association with the effectiveness and safety/tolerability of the tested medications has completely been neglected.